Prognostic Markers Of Resistance And Relapse In Acute Leukaemia - Pon, Maha Abdullah@Maha-Lakswmi (2003)
Leukaemia is the malignant transformation of cells of the haemopoietic system. It is the most common cancer in children. The Ministry of Health, Malaysia (1999) reported an incidence rate of 3.36 in every 100,000. Nevertheless, leukaemia is nine times more frequent in adults. It is differentiated into acute and chronic leukaemia by morphology of the cell. Acute leukaemia is also a more aggressive disease. Chronic leukaemia is rare among children. The majority of leukaemia (83%) is acute leukaemia (National Cancer Registry, Malaysia, 2002). The two main cell types are the lymphoid and myeloid lineage. The conventional method for the treatment of acute leukaemia is chemotherapy. Children achieve a remission rate of > 90%. In adult acute lymphoblastic leukaemia (ALL) remission is only 65-80%. Response rate is worst among adults with acute myeloid leukaemia (AML), 70% in young adults decreasing to 25% in the elderly. The rest are resistant to treatment.